Działalność administracji publicznej w orzecznictwie sądowym - Kiczka, Karol (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Judicial decisions shape legal order and fix rights and obligations of an entity as well as the tasks and competences of an administrative organ. The paper aims to present the significance of jurisdiction of European Union and Member States in the process of legislation and also in applying and enforcing the law. Judicial authorities ensure respect of the rule of law in democratic states and in civil market economy. Judicial decisions are an adjuvant factor for shaping the legal order.
Keywords: administrative court; entity in administrative law; jurisdiction; internal market; organ of public administration